34.3k views
1 vote
Look at the proof showing sin^4 x = 3 - 4 cos 2x + cos 4x / 8. Which expression will complete the fourth step of the proof ?

Look at the proof showing sin^4 x = 3 - 4 cos 2x + cos 4x / 8. Which expression will-example-1
User Jmster
by
5.7k points

1 Answer

2 votes

Answer:

The answer is the first one ⇒
(1-2cos2x+(1+cos4x)/(2))/(4)

Explanation:

∵ cos4x = 2cos²2x - 1

∴ cos²2x = (1 + cos4x)/2


sinx^(4)x=(1-2cos2x+(1+cos4x)/(2))/(4) ⇒ ×2 up and down


=(2-4cos2x+1+cos4x)/(8)


=(3-4cos2x+cos4x)/(8)

User Bojian Zheng
by
6.3k points